Development of High Antioxidant Red Palm Oil Cake as a Potential Functional Food - Harianti, Rini; Marliyati, Sri Anna; Rimbawan, Rimbawan; Sukandar, Dadang (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2018)
This study aimed to develop high antioxidant cake product with red palm oil (RPO) content to substitute the use of margarine as a potential functional food. This study used a complete randomized design with four levels of RPO substitution for margarine, namely F0 (0:100), F1 (80:20), F2 (90:10), and F3 (100:0). Organoleptic results showed that high antioxidant cake F3 was best in which also contained the highest RPO addition level. The high antioxidant cake F3 had yellow colour, hardness of 650.67 gf, bulk density of 0.27 g/ml, 4.31% moisture, 1.48% ash, 21.66% fat, 9.76% protein, 62.80% carbohydrate, 40.74 ppm/100 g β-carotene, and the 470.44 mg/100 g antioxidant activity. Thus the product can be categorized as high in β-carotene. Therefore, this product has a potential to be a functional food options, especially for atherosclerosis prevention.